The sin of Madelon Claudet [videorecording (DVD)] - Selwyn, Edgar, 1875-1944; Hayes, Helen, 1900-1993; Stone, Lewis, 1879-1953; Hamilton, Neil, 1899-1984; Edwards, Cliff, 1895-1971; Knoblock, Edward, 1874-1945 (Warner Home Video, 2011)
An abandoned young mother whose devotion to her child and her desperate sacrifices to provide for him lead her into harlotry.